THE ROLE OF ARTIFICIAL INTELLIGENCE IN MENTAL HEALTH SUPPORT: OPPORTUNITIES AND ETHICAL CHALLENGES - Gulomova Fatima Alisher kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. This article examines the role of artificial intelligence in mental health support, focusing on both its practical opportunities and ethical challenges. AI-based systems, including conversational agents, digital screening tools, predictive analytics and large language models, are increasingly being used to support mental health care, improve  access  to  psychological  information,  assist  clinicians  and  personalize interventions.